Vitamin D status in chronic fatigue syndrome/myalgic encephalomyelitis: a cohort study from the North-West of England. Issue 11 (8th November 2017) - Earl, Kate E; Sakellariou, Giorgos K; Sinclair, Melanie; Fenech, Manuel; Croden, Fiona; Owens, Daniel J; Tang, Jonathan; Miller, Alastair; Lawton, Clare; Dye, Louise; Close, Graeme L; Fraser, William D; et al.
Abstract : Objective: Severe vitamin D deficiency is a recognised cause of skeletal muscle fatigue and myopathy. The aim of this study was to examine whether chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is associated with altered circulating vitamin D metabolites. Design: Cohort study. Setting: UK university hospital, recruiting from April 2014 to April 2015. Participants: Ninety-two patients with CFS/ME and 94 age-matched healthy controls (HCs). Main outcome measures: The presence of a significant association between CFS/ME, fatigue and vitamin D measures. Results: No evidence of a deficiency in serum total 25(OH) vitamin D (25(OH)D2 and 25(OH)D3 metabolites) was evident in individuals with CFS/ME. Liquid chromatography tandem mass spectrometry (LC–MS/MS) analysis revealed that total 25(OH)D was significantly higher (p=0.001) in serum of patients with CFS/ME compared with HCs (60.2 and 47.3 nmol/L, respectively). Analysis of food/supplement diaries with WinDiets revealed that the higher total 25(OH) vitamin D concentrations observed in the CFS/ME group were associated with increased vitamin D intake through use of supplements compared with the control group. Analysis of Chalder Fatigue Questionnaire data revealed no association between perceived fatigue and vitamin D levels. Conclusions: Low serum concentrations of total 25(OH)D do not appear to be a contributing factor to the level of fatigue of CFS/ME.